2017
DOI: 10.1167/iovs.17-21969
|View full text |Cite
|
Sign up to set email alerts
|

Parafoveal Photoreceptor Abnormalities in Asymptomatic Patients With RP1L1 Mutations in Families With Occult Macular Dystrophy

Abstract: The sparing of the central foveal photoreceptor layer accounts for the well-preserved visual acuity in the asymptomatic patients. The sparing may represent either the initial phase of typical OMD or a subtype of macular lesion associated with OMD. It is necessary to examine asymptomatic subjects in families with OMD because some of them may progress to the typical phenotype of OMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…31 Thus far, only 11 patients from 6 families with biallelic POC1B variants have been reported to have retinal abnormalities except in the Japanese patients (Table 6). [27][28][29][30][31]33 We have presented eight Japanese patients from seven families. According to previous reports, a wide variety of phenotypes were observed: one case of LCA, seven cases of CORD, and three cases of COD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Thus far, only 11 patients from 6 families with biallelic POC1B variants have been reported to have retinal abnormalities except in the Japanese patients (Table 6). [27][28][29][30][31]33 We have presented eight Japanese patients from seven families. According to previous reports, a wide variety of phenotypes were observed: one case of LCA, seven cases of CORD, and three cases of COD.…”
Section: Discussionmentioning
confidence: 99%
“…SD-OCT images were obtained, and cross-sectional images based on the gray scales along a selected line were generated according to a published method with custom-made software (Longitudinal profiling version 0.1). 33 The presence of highintensity lines shown as peaks in the cross-sectional images were assessed for this study.…”
Section: Signal Intensity Profiling Of Faf and Sd-oct Imagesmentioning
confidence: 99%
“…13,14 The OCT findings play an important role in the diagnosis of OMD. 5,11,15,16 In an earlier report of a large family having the RP1L1 gene mutation (p.Arg45Trp), Tsunoda et al 5 documented that the photoreceptor structures, assessed by OCT, gradually changed during the course of OMD.…”
mentioning
confidence: 99%
“…The vari-ant p.S1199C is not found in the ExAC or 1000 Genomes Project database, but all 12 reported patients harboring this variant were East Asian. 4,19,20 This indicated that these two variants were more common in the East Asian population than in other populations. Previous studies showed that the penetrance of the variant p.R45W was incomplete, ranging from 38% to 85%.…”
Section: Discussionmentioning
confidence: 96%
“…The IZ absence and EZ blurring of photoreceptor microstructures observed by SD-OCT are classical changes in OMD patients and were observed in all probands of our cohort. However, Kato et al 20 found that central foveal microstructures could be spared in some patients carrying pathogenic RP1L1 variants; the visual acuity of these patients was generally well preserved, and mfERG results could even be normal, but SD-OCT revealed abnormal microstructures in the parafoveal regions. This finding demonstrated that SD-OCT is more sensitive in detecting pathologic changes of OMD than other examination methods and contributes to the improvement of early diagnostics.…”
Section: Discussionmentioning
confidence: 99%